Assessing the Effectiveness of Settling Indonesian Sea Border Disputes through Litigation and Non-Litigation Paths - Izzati, Nur Arissa; Permata, Chusnul Qotimah Nita; Santalia, Miftah (Universitas Negeri Semarang, 2020)
The Border disputes between sea, island and the state are matters of international courts through the role of international law. Sea boundary problems often occur such as disputes between Indonesia and Vietnam in the Natuna Sea region, disputes over the Exclusive Economic Zone (EEZ), disputes between Indonesia and Malaysia in the Malacca Strait, South China Sea Disputes, etc. Unilateral claims cause relations between countries experiencing conflict. This happens because negotiations between countries have not been completed, violations by disputed countries, unclear sea boundaries, etc. The United Nations Convention on the Law of the Sea (UNCLOS) 1982 is an international maritime law that only applies to ratify countries that can apply it. Settlement can be donethrough two channels, that are litigation and non-litigation, ITOLS is the last attempt at completion of the litigation path.